Lifetime employment in Japan: Concepts and measurements - Hiroshi Ono (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
This paper poses three fundamental questions about lifetime employment in Japan: How big is it? How unique is it? And, how is it changing? I examine different concepts and methods for estimating lifetime employment and conclude that it covers roughly 20 percent of the Japanese labor force. Job mobility remains considerably lower in Japan than in other economies (particularly the U.S.). Evidence regarding changes in lifetime employment is mixed. The share of workers in the core, an ex-ante measure of lifetime employment, is declining. But the probability of job separations has remained stable for those who are already in the system. I also find evidence that the incentives among workers, managers and executives are aligned to preserve the lifetime employment system.
Keywords: J24; J42; J62; 330; Lifetime employment; job mobility; Erwerbspersonenpotenzial; Arbeitsbeziehungen; Arbeitsmobilität; Betriebszugehörigkeit; Japan